Entre giro emocional y reenactment. Presentismo y usos del pasado en los debates memoriales de los años 2000 en España - Mercedes Yusta Rodrigo (Cahiers de Civilisation Espagnole Contemporaine)
Based on a reflection on presentism, this text is interested in the uses of memory in Spain at the beginning of the 21st century, in particular around the so-called ‘recovery of historical memory’, which encompasses the uses of the past, memorial discourses and political and judicial claims carried out by the victims of Franco's dictatorship and their descendants. The analysis of these uses takes into account the ‘emotional turn’ in the social sciences and proposes a new interpretation of the presence of the past in the political debates and social practices of contemporary Spain as a reenactment, which not only brings the past into the present but also transforms its meaning, with undeniable political consequences.